2015
DOI: 10.1155/2015/725989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alcian Blue, Trypan Blue, and Toluidine Blue for Visualization of the Primo Vascular System Floating in Lymph Ducts

Abstract: The primo vascular system (PVS), floating in lymph ducts, was too transparent to be observed by using a stereomicroscope. It was only detectable with the aid of staining dyes, for instance, Alcian blue, which was injected into the lymph nodes. Some dyes were absorbed preferentially by the PVS than the lymph wall. It remains a standing problem to know what dyes are absorbed better by the PVS than the lymph walls. Such information would be useful to unravel the biochemical properties of the PVS that are badly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Then the skin was opened to two sides, respectively, the inguinal (IN) lymph nodes were bilateral and close to the bifurcation of the superficial epigastric veins. 36 After the exposure of IN lymph nodes, the NIR polymer dots (∼13 μg, 50 μL) were injected into the nodes of both sides, and the setting and analysis of in vivo fluorescence imaging was conducted as the same method. 33 2.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the skin was opened to two sides, respectively, the inguinal (IN) lymph nodes were bilateral and close to the bifurcation of the superficial epigastric veins. 36 After the exposure of IN lymph nodes, the NIR polymer dots (∼13 μg, 50 μL) were injected into the nodes of both sides, and the setting and analysis of in vivo fluorescence imaging was conducted as the same method. 33 2.5.…”
Section: Methodsmentioning
confidence: 99%
“…The vertical incision was made from the navel toward the midpoint of the clavicle along the ventral surface, and four horizontal incisions were made along the clavicles and pelvis. Then the skin was opened to two sides, respectively, the inguinal (IN) lymph nodes were bilateral and close to the bifurcation of the superficial epigastric veins . After the exposure of IN lymph nodes, the NIR polymer dots (∼13 μg, 50 μL) were injected into the nodes of both sides, and the setting and analysis of in vivo fluorescence imaging was conducted as the same method …”
Section: Methodsmentioning
confidence: 99%
“…The re-emergence of PVS research has focused primarily on visualizing and characterizing the various PV subtypes reported by Kim. The majority of studies describe the utilization of different dyes and techniques to provide contrast to the five PV subtypes, including ILVPVs 7,9,10,[25][26][27][28][29] . Once an ILVPV has been stained with a dye and visualized with the aid of a microscope, the PV is harvested and immunohistochemical techniques are utilized to further identify the structure.…”
Section: Characterization Of Ilvpvsmentioning
confidence: 99%
“…Over the past twenty years, more than one hundred papers have been published in international academic journals, including ones registered with SCI (E) and SCOPUS, by the PVS group. For example, the group reported that they had succeeded in identifying the structures, which the BK group claimed to have found, in the lymphatic system [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and the blood system [25][26][27][28], on the surfaces of internal organs [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and inside the nervous system [46][47][48][49][50][51][52][53][54][55]. In addition, they hypothesized that the structures might ...…”
Section: Introductionmentioning
confidence: 99%